Transmission electron microscopy study of microstructural properties and dislocation characterization in the GaN film grown on the cone-shaped patterned Al2O3 substrate. (9th October 2013) - Park, Jung Sik; Yang, Jun-Mo; Park, Kyung Jin; Park, Yun Chang; Yoo, Jung Ho; Jeong, Chil Seong; Park, Jucheol; He, Yinsheng; Shin, Keesam
Abstract: Growing a GaN film on a patterned Al2 O3 substrate is one of the methods of reducing threading dislocations (TDs), which can significantly deteriorate the performance of GaN-based LEDs. In this study, the microstructural details of the GaN film grown on a cone-shaped patterned Al2 O3 substrate were investigated using high-resolution transmission electron microscopy and weak-beam dark-field techniques. Various defects such as misfit dislocations (MDs), recrystallized GaN (R-GaN) islands and nano-voids were observed on the patterned Al2 O3 surfaces, i.e. the flat surface (FS), the inclined surface (IS) and the top surface (TS), respectively. Especially, the crystallographic orientation of R-GaN between the GaN film and the inclined Al2 O3 substrate was identified as $[\overline 1 2\overline 1 0]_{{\rm GaN}} \hbox{//}[\overline 1 101]_{{\rm R - GaN} \, {\rm on}\, {\rm IS}} \hbox{//}[\overline 1 100]_{ {{\rm Al}} _{\rm 2} {\rm O}_{\rm 3}} $, $(\overline 1 012)_{{\rm GaN}} \hbox{//}(1\overline 1 02)_{{\rm R - Ga}\, {\rm Non}\, {\rm IS}} \hbox{//}(\overline {11} 26)_{ {{\rm Al}} _{\rm 2} {\rm O}_{\rm 3}} $ . In addition, a rotation by 9° between $(10\overline 1 1)_{{\rm R - GaN}} $ and $(0002)_{{\rm GaN}} $ and between $(10\overline 1 1)_{{\rm R - GaN}} $ and $(0006)_{ {{\rm Al}} _{\rm 2} {\rm O}_{\rm 3}} $ was found to reduce the lattice mismatch between the GaN film and the Al2 O3 substrate. Many TDs in the GaN film were observed on the FS and TS of Al2 O3 . However, few TDs were observed on the IS. Most of the TDs generated from the FS of Al2 O3 were bent to the inclined facet rather than propagating to the GaN surface, resulting in a reduction in the dislocation density. Most of the TDs generated from the TS of Al2 O3 were characterized as edge dislocations.